Citizenship and the Idea of Freedom/ Liberation in the Post-Modern Period: A Particular Reference to Algeria - Boudersa, Hemza (جامعة الأمير عبد القادر للعلوم الإسلامية - كلية أصول الدين, 2023)
الهدف الأولي لهذا البحث هو التركيز على البعد الواقعي لكل مضامين الحرية ومعانيها. في نفس السياق، تقابل كل معاني الحرية بأخرى مضادة مثل: القيد، الضرورة والحتمية. تصنف عدة مراجع ومنها مؤلف زكريا إبراهيم الموسوم ب مشكلات فلسفية: إشكالية الحرية، الحرية إلى نوعين: حرية التصميم وحرية التنفيذ. تشير هذه الورقة البحثية إلى إشكالية الحرية وفقدانها مع الإشارة إلى المدارس المدافعة/ الداحضة لكل فكر مع الإشارة إلى إشكالية المواطنة من حيث أنها مشجع على عملية التحرر أو داحض للحرية من أصلها. تكشف نتائج البحث وتؤكد على أن واقعية الطرح الفلسفي تتطلب اعتبار الحرية عملية تحرر داخلي وخارجي مستمر وليس منتوج نفسي جاهز أو مجهز. تركز الورقة البحثية مع التوصية على دور التربية المهم في عملية التحرر بكل أبعاده وأطيافه. The primary objective of this research is to focus on the realistic dimensions of all the insights and meanings of freedom. In the same respect, some countermeasures, namely constraints, necessities, and determinism encounter all meanings of freedom in a way or another. Many references, namely ZAKARIYA Ibrahim's book Philosophical Issues: the Problem of Freedom classified freedom into two types: (1) Freedom of Planning and (2) Freedom of doing or acting. The issue of freedom revolves as well around two visions: Freedom Affirmers (defenders) and Freedom Refuters with reference to the extent to which citizenship is either liberation booster or freedom constrainer. Findings of the paper reveal initially the freedom is a continuous process to achieve, not a final product attain. Education plays/recommended to play a great role in promoting the process of emancipation in all its multidimensional prisms or perspectives.
Keywords: قيم المواطنة -- ما بعد الحداثة -- الفكر الفلسفي -- الجزائر